Ultralight porous carbon material and preparation method and application thereof

By modifying composite hydroxylated multi-walled carbon nanotubes and linear acetylene carbon, ultralight porous carbon materials with composite porous structures were prepared, which solved the problem of increased indoor radon concentration, achieved efficient adsorption of radon gas, protected human health and met environmental protection requirements.

CN119750541APending Publication Date: 2025-04-04SHANGHAI XINNENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411850994.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The indoor radon concentration has increased significantly, resulting in respiratory diseases and heavy metal poisoning, and it is difficult for the existing technology to effectively absorb radon.

Method used

Ultralight porous carbon materials with composite porous structures are prepared by modifying hydroxylated multi-walled carbon nanotubes and linear acetylene carbon carbon to prepare carbon materials with a large specific surface area and light density, and use them to efficiently adsorb radon gas in the air.

Benefits of technology

It has achieved efficient adsorption of indoor radon, significantly improved the radon absorption efficiency, protected human health, and was also green and environmentally friendly with ultra-light porous carbon materials, without additional pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190580560000071
    Figure BDA0005190580560000071
  • Figure BDA0005190580560000081
    Figure BDA0005190580560000081
  • Figure BDA0005190580560000101
    Figure BDA0005190580560000101
Patent Text Reader

Abstract

The present invention relates to an ultralight porous carbon material and a preparation method and application thereof, belonging to the technical field of ultralight carbon materials. The ultralight porous carbon material of the present invention is a composite porous structure, including macropores with pore diameters of 30nm to 200nm, mesopores with pore diameters of 2nm to 30nm, and micropores with pore diameters of 1nm to 2nm; the specific surface area of ​​the ultralight porous carbon material is 2000m 2 / g~3000m 2 / g, and the relative density is 0.65-0.90. The carbon material prepared by the present invention has a composite porous structure and a large specific surface area, and can efficiently adsorb the polluted gas radon in the air, showing excellent adsorption efficiency. At the same time, the material is green, environmentally friendly, non-toxic and harmless, and will not generate additional pollution during use, which meets the requirements of sustainable development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ultralight carbon materials, and in particular relates to an ultralight porous carbon material and a preparation method and application thereof. Background Art

[0002] Radon is a colorless, odorless, radioactive inert gas. The main reason for the presence of radon indoors is the natural release from the soil and the slow release from building materials. The decay of radioactive elements such as radium in the soil will produce radon gas, which diffuses to the ground through pores and cracks in the soil and may enter the room through the foundation of the building, basement, ground cracks, etc. Using materials containing radioactive substances as wall building materials or using stones with high radioactive substances such as granite and marble as interior decoration materials, these materials contain a certain concentration of radon. 226 Radium will slowly decay and produce radon, which will be released into the room, causing a significant increase in the concentration of radon in the room. The main harm of radon is that it enters the human lungs through breathing, causing respiratory diseases. In addition, radon gas has dual harmfulness: one is the alpha particle radiation damage produced by its direct decay, and the other is that the decay product lead may cause heavy metal poisoning.

[0003] In view of this, there is a need to provide an ultra-light porous carbon material that is beneficial for absorbing radon and a preparation method and application thereof to solve the above-mentioned technical gap problem. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide an ultralight porous carbon material and a preparation method and application thereof. The present invention provides an ultralight porous carbon material, the prepared carbon material has a composite porous structure and a large specific surface area, can efficiently adsorb polluted gas radon in the air, and exhibits excellent adsorption efficiency. The ultralight porous carbon material prepared by the present invention is green, environmentally friendly, non-toxic and harmless, and will not generate additional pollution during use, meeting the requirements of sustainable development.

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide an ultra-light porous carbon material and a preparation method and application thereof.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] The first object of the present invention is to provide an ultralight porous carbon material, wherein the ultralight porous carbon material has a composite porous structure, including macropores with pore sizes of 30nm to 200nm, mesopores with pore sizes of 2nm to 30nm, and micropores with pore sizes of 1nm to 2nm; the specific surface area of ​​the ultralight porous carbon material is 2000m 2 / g~3000m 2 / g, relative density is 0.65~0.90.

[0008] The beneficial effects of the present invention are as follows: the ultralight porous carbon material of the present invention has a porous structure, a large specific surface area, and a light density, and these characteristics enhance the ability of the ultralight porous carbon material to absorb radon.

[0009] Based on the above technical solution, the present invention can also be improved as follows.

[0010] A second object of the present invention is to provide a method for preparing an ultralight porous carbon material, comprising the following steps:

[0011] (1) mixing hydroxylated multi-walled carbon nanotubes with straight-chain acetylene carbon, adding an organic additive, heating in an oil bath and stirring to obtain a sol-like carbon material mixture; adding a modified molecular sieve to the sol-like carbon material mixture and calcining the mixture to obtain a calcined carbon material mixture;

[0012] (2) mixing the calcined carbon material mixture with a metal salt solution and reacting the mixture in a high-pressure reactor to obtain a reacted carbon material mixture;

[0013] (3) The carbon material mixture after the reaction is sequentially subjected to alkali washing, acid washing, water washing, impurity removal and drying to finally obtain an ultra-light porous carbon material.

[0014] The beneficial effect of adopting the above further scheme is that the hydroxylated multi-walled carbon nanotubes themselves as environmentally friendly materials have good adsorption performance and plasticity, and the isotope 13 The straight-chain acetylene carbon with C as raw material has better strength and stability, and is non-radioactive, and can effectively avoid the negative impact on human health. 12 Hydroxylated multi-walled carbon nanotubes with C as raw material 13 The straight-chain acetylene carbon with C as raw material is modified and compounded to prepare an ultra-light porous carbon material that is beneficial for absorbing radon. It can not only greatly improve the efficiency of absorbing common pollutants in the indoor environment, but also further absorb the difficult-to-remove radioactive gas radon.

[0015] The ultra-light porous carbon material prepared by the above steps has a porous structure, a large specific surface area, and a light density. It can not only greatly improve the efficiency of absorbing common pollutants in the indoor environment, but also further absorb the difficult-to-remove radioactive gas radon.

[0016] Furthermore, in step (1), the weight components of the hydroxylated multi-walled carbon nanotubes and the linear acetylene carbon are 4-8 parts and 1-3 parts respectively; the carbon content of the hydroxylated multi-walled carbon nanotubes is 90%-95%; the carbon content of the linear acetylene carbon is 90%-95%; wherein the raw material of the hydroxylated multi-walled carbon nanotubes is 12 C; the raw material of the straight chain acetylene carbon is 13 C

[0017] The beneficial effect of adopting the above further scheme is: selecting hydroxylated multi-walled carbon nanotubes with high carbon content ( 12 C), the purpose is that it is formed by curling multiple layers of graphite sheets and presents a hollow tube shape. The layers interact with each other through van der Waals forces, which greatly improves the adsorption efficiency. The straight-chain acetylene carbon with high carbon content ( 13 C), because its structure is a straight-chain carbon-carbon triple bond, which has high chemical activity and is conducive to the adsorption of inert pollutants; and the ultra-light porous carbon material made according to the above composition is more effective in absorbing radon.

[0018] Furthermore, in step (1), the mass ratio of the organic auxiliary agent to the mixture is 10-15:50; the organic auxiliary agent is a mixed solution of epoxy organic amine and nitrilotriacetic acid, and the mass ratio of the epoxy organic amine to the nitrilotriacetic acid is 1:5-10.

[0019] The beneficial effect of adopting the above further scheme is that the polarity of the organic additive selected in the present invention can promote the dissolution of impurities present in the carbon material, such as metal oxides, inorganic salts, etc.

[0020] Furthermore, the oil bath heating temperature is 150°C to 170°C and the heating time is 10h to 12h.

[0021] The beneficial effect of adopting the above further scheme is that under the above mass ratio and oil bath heating method, 12 Hydroxylated multi-walled carbon nanotubes and 13 The straight-chain acetylene carbon with C as the raw material is fully mixed to form a sol-like carbon material mixture.

[0022] Furthermore, in step (1), the weight ratio of the sol-like carbon material mixture to the modified molecular sieve is 9-10:0.5-0.8; and the modified molecular sieve is HZSM-5 molecular sieve.

[0023] Furthermore, the modified molecular sieve is HZSM-5 molecular sieve powder with a silicon-aluminum ratio of 200 to 1000 and a pore size of 0.53*0.56nm or 0.51*0.55nm.

[0024] The beneficial effect of adopting the above further scheme is: using the modified molecular sieve HZSM-5 as a carrier of the carbon material mixture, it can not only play the role of supporting the carbon material, but also play a catalytic effect, further improving the reaction efficiency.

[0025] Furthermore, before adding the modified molecular sieve powder to the sol-like carbon material mixture, ammonia water or sodium bicarbonate is also added dropwise to adjust the pH of the sol-like carbon material mixture to 7.0-7.8.

[0026] The beneficial effect of adopting the above further scheme is: using ammonia water or sodium bicarbonate as a pH regulator is to provide a good reaction environment for the sol-like carbon material mixture in a weakly alkaline environment of pH 7.0-7.8, thereby improving the subsequent reaction efficiency.

[0027] Furthermore, the calcination temperature in step (1) is 400° C. to 500° C., and the calcination time is 48 h to 96 h.

[0028] The beneficial effects of adopting the above further scheme are: the purpose of the long-term calcination in the present invention is to ensure that the reaction can proceed fully; the purpose of the vacuum is to prevent the carbon material mixture from being oxidized under high temperature conditions.

[0029] Furthermore, the present invention adopts a muffle furnace for calcination.

[0030] The beneficial effect of adopting the above further scheme is that the use of a muffle furnace for calcination can rapidly increase the reaction temperature and accurately control the temperature range, thereby stimulating the catalytic activity of HZSM-5 and allowing the carbon material mixture to be heated evenly.

[0031] Furthermore, the reaction conditions in step (2) are as follows: the pressure during the reaction is 15 MPa to 25 MPa, the temperature is 150° C. to 200° C., and the time is 24 h to 36 h.

[0032] The beneficial effect of adopting the above further scheme is that the present invention uses a high-pressure reactor as a reaction vessel, which can allow the components to react fully by increasing the pressure, and at the same time, can effectively improve the reaction efficiency and conversion rate within the range of pressure, temperature and time conditions.

[0033] Furthermore, the metal salt solution in step (2) is calcium phytate; the mass ratio of the calcined carbon material mixture to the metal salt solution is (10-20):1; and the concentration of the metal salt is 0.01 mol / L-0.05 mol / L.

[0034] The beneficial effect of adopting the above further scheme is that: the present invention selects calcium phytate for reaction, and the calcium ions contained in it have good adsorption effect, which is more conducive to absorbing radon through ion exchange and other methods.

[0035] Furthermore, the calcined carbon material mixture needs to be ground into powder of 100-150 meshes before being mixed with the metal salt solution, and then mixed with water.

[0036] The beneficial effect of adopting the above further scheme is that grinding the calcined carbon material mixture into fine powder can increase its specific surface area and voids, which is conducive to the introduction of calcium ions into the voids, thereby improving the absorption efficiency.

[0037] Furthermore, the dosage ratio of the powder to the water is 1:50-100.

[0038] Furthermore, the alkaline solution used for the alkali washing is a tetramethylammonium hydroxide solution; the mass ratio of the alkaline solution to the carbon material mixture after the reaction is (25-50):1; the acid solution used for the acid washing is a dimethylbenzenesulfonic acid solution, and the mass ratio of the acid solution to the carbon material mixture after the alkali washing is (15-30):1.

[0039] The beneficial effect of adopting the above further scheme is: using tetramethylammonium hydroxide solution as the alkaline solution, the purpose is to remove other residual organic matter and possible grease and the like.

[0040] Furthermore, the alkali washing soaking time is 12 to 24 hours; the acid washing soaking time is 12 to 24 hours.

[0041] The beneficial effect of adopting the above further scheme is that the concentration of the acid and alkali solution and the immersion time are controlled within the above condition range to ensure that the acid and alkali washing can be carried out thoroughly to improve the purity of the final ultra-light porous carbon material.

[0042] Furthermore, the carbon material mixture after the reaction needs to be cooled to 20-25° C. before the alkali washing and soaking, and the carbon material mixture after the alkali washing and soaking needs to be heated to 60-80° C. before the acid washing and soaking.

[0043] The beneficial effects of adopting the above further scheme are: lowering the temperature can ensure the stability of the liquid system during alkali washing, and raising the temperature to a certain extent during acid washing to ensure that the residual impurities, excess alkali and inorganic salts in the liquid system are completely decomposed.

[0044] The third object of the present invention is to provide an application of an ultra-light porous carbon material, wherein the ultra-light porous carbon material is used to absorb polluted gas radon.

[0045] The beneficial effects of the present invention are as follows: the ultralight porous carbon material prepared by the present invention protects human health by absorbing free radon gas existing in the room, avoiding the induction of diseases and heavy metal poisoning, and the ultralight porous carbon material itself is green and environmentally friendly, and no additional pollution is generated during the overall absorption process. DETAILED DESCRIPTION

[0046] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.

[0047] Example 1: Preparation of ultralight porous carbon material

[0048] (1) In 5.3 parts by weight of a carbon content of 90% to 95% 12 C as raw material hydroxylated multi-walled carbon nanotubes, 2.1 parts by weight of carbon containing 90% to 95% 13 A mixed solution of epoxy organic amine and nitrilotriacetic acid is added to a mixture of straight-chain acetylene carbon with C as a raw material, the mass ratio of which is 1:5 (the mass ratio of the organic auxiliary agent to the mixture is 12:50), and the mixture is evenly mixed, and heated and stirred in an oil bath for 10 hours at a temperature of 160°C to obtain a sol-like carbon material mixture; 9.2 parts by weight of the prepared sol-like carbon material mixture is dripped with ammonia water, the pH is adjusted to 7.5, 0.6 parts by weight of a modified molecular sieve HZSM-5 powder with a silicon-aluminum ratio of 800 and a pore size of 0.53*0.56nm is added, and vacuum is drawn, and the mixture is placed in a muffle furnace for calcination at a temperature of 480°C and a calcination time of 72 hours to obtain a calcined carbon material mixture;

[0049] (2) grinding the calcined carbon material mixture into a powder of about 120 mesh, mixing it with deionized water at a ratio of 1:50, adding a 0.01 mol / L calcium phytate solution with a mass ratio of 1:20 to the carbon material powder, and placing it in a high-pressure reactor for further reaction at a pressure of 22 MPa, a temperature of 175° C., and a reaction time of 36 h to obtain a reacted carbon material mixture;

[0050] (3) The carbon material mixture after the reaction is cooled to 25°C, and an alkali washing and soaking operation is performed. A 1 mol / L tetramethylammonium hydroxide solution is selected, and the mass ratio of the tetramethylammonium hydroxide solution to the carbon material mixture is 30:1. The soaking time is 15 hours to obtain the carbon material mixture after alkali washing and soaking; then the carbon material mixture after alkali washing and soaking is heated to 75°C, and a dimethylbenzenesulfonic acid solution with a molar concentration of 8% is added for acid washing and soaking. The mass ratio of the tetramethylammonium hydroxide solution to the carbon material mixture is 25:1. The mixture is soaked for 24 hours to obtain the carbon material mixture after acid washing and soaking. After the acid washing is completed, the carbon material mixture is washed, impurities are removed, and dried in turn with deionized water to obtain the ultra-light porous carbon material.

[0051] Embodiment 2-3:

[0052] Embodiment 2-3 is the same as embodiment 1, the difference being that 12 Hydroxylated multi-walled carbon nanotubes made from C, 13 C is the difference in the amount of straight-chain acetylene carbon added as the raw material, and the other raw materials and steps are the same as those in Example 1. The amount of carbon material added in Examples 2-3 is shown in Table 1:

[0053] Table 1

[0054]

[0055]

[0056] Comparative Example 1: Preparation of ultralight porous carbon material

[0057] This comparative example is the same as Example 1, except that the modified molecular sieve HZSM-5 powder is not added in step (1), and the remaining raw materials and steps are the same as those in Example 1. Step (1) is specifically as follows:

[0058] (1) In 5.3 parts by weight of a carbon content of 90% to 95% 12 C as raw material hydroxylated multi-walled carbon nanotubes, 2.1 parts by weight of carbon containing 90% to 95% 13 A mixed solution of epoxy organic amine and nitrilotriacetic acid is added to a mixture of straight-chain acetylene carbon with C as the raw material in a mass ratio of 1:5 (the mass ratio of the organic auxiliary agent to the mixture is 12:25), and the mixture is evenly mixed. The mixture is heated and stirred in an oil bath for 10 hours at a temperature of 160°C to obtain a sol-like carbon material mixture; 9.2 weight parts of the obtained sol-like carbon material mixture is dripped with ammonia water, the pH is adjusted to 7.5, and after vacuuming, it is placed in a muffle furnace for calcination at a temperature of 480°C and a calcination time of 72 hours to obtain a calcined carbon material mixture.

[0059] Comparative Example 2: Preparation of ultralight porous carbon material

[0060] This comparative example is the same as Example 1, the only difference being that the calcination temperature in step (1) is different, and the other raw materials and steps are the same as those in Example 1. Step (1) is specifically as follows:

[0061] (1) In 5.3 parts by weight of a carbon content of 90% to 95% 12 C as raw material hydroxylated multi-walled carbon nanotubes, 2.1 parts by weight of carbon containing 90% to 95% 13 A mixed solution of epoxy organic amine and nitrilotriacetic acid is added to a mixture of straight-chain acetylene carbon with C as raw material, with a mass ratio of 1:5 (the mass ratio of organic auxiliary agent to the mixture is 12:25), and mixed evenly, heated and stirred in an oil bath, the heating time is 10 hours, and the temperature is 160°C to obtain a sol-like carbon material mixture; 9.2 parts by weight of the prepared sol-like carbon material mixture is dripped with ammonia water, the pH is adjusted to 7.5, 0.6 parts by weight of modified molecular sieve HZSM-5 powder with a silicon-aluminum ratio of 800 and a pore size of 0.53*0.56nm is added, and after vacuuming, it is placed in a muffle furnace for calcination at a temperature of 160°C and a calcination time of 10 hours. A calcined carbon material mixture is obtained.

[0062] Comparative Example 3: Preparation of ultralight porous carbon material

[0063] This comparative example is the same as Example 1, the only difference being that the pressure in the autoclave in step (2) is different, and the other raw materials and steps are the same as those in Example 1. Step (2) is specifically as follows:

[0064] (2) The calcined carbon material mixture is ground into a powder of about 120 mesh, mixed with deionized water at a ratio of 1:50, and mixed with a 0.01 mol / L calcium phytate solution at a mass ratio of 1:20 to the carbon material powder, and placed in a high-pressure reactor for further reaction at a pressure of 5 MPa, a temperature of 175°C, and a reaction time of 36 h to obtain a reacted carbon material mixture.

[0065] Comparative Example 4: Preparation of ultralight porous carbon material

[0066] This comparative example is the same as Example 1, except that step (1) does not contain 13 C is the straight-chain acetylene carbon of the raw material, and the other raw materials and steps are the same as those in Example 1. Step (1) is as follows:

[0067] (1) In 5.3 parts by weight of a carbon content of 90% to 95% 12 A mixed solution of epoxy organic amine and nitrilotriacetic acid was added to the hydroxylated multi-walled carbon nanotubes with C as the raw material, with a mass ratio of 1:5 (the amount of the organic auxiliary agent added was consistent with that in Example 1), and the mixture was evenly mixed, heated and stirred in an oil bath, the heating time was 10 hours, and the temperature was 160°C to obtain a sol-like carbon material mixture; 9.2 parts by weight of the obtained sol-like carbon material mixture was dripped with ammonia water, the pH was adjusted to 7.5, 0.6 parts by weight of a modified molecular sieve HZSM-5 powder with a silicon-aluminum ratio of 800 and a pore size of 0.53*0.56nm was added, and after vacuuming, the mixture was placed in a muffle furnace for calcination at a temperature of 480°C and a calcination time of 72 hours. The calcined carbon material mixture was obtained.

[0068] Test example:

[0069] After testing the radon content in a newly renovated house, the ultralight porous carbon materials prepared in Examples 1-3 and Comparative Examples 1-4 were used for treatment to verify their radon absorption effects. The testing method steps are as follows:

[0070] (1) Place the ultra-light porous carbon material evenly in every corner of the house, 1 meter above the ground, for 7 days, and allow the house to be naturally ventilated;

[0071] (2) Sampling and testing of radon gas in indoor environment before and after absorption and treatment shall be carried out according to the requirements and methods for the determination of radon in Appendix H of GBT18883-2022.

[0072] Table 2

[0073]

[0074] From Table 2, we can get:

[0075] (1) The efficiency of the ultralight porous carbon materials prepared in Examples 1-3 in absorbing radon in the house is 90%. Comparison between Comparative Example 1 and Example 1 shows that in the process of preparing the ultralight porous carbon material, if the modified molecular sieve HZSM-5 powder is not added, the corresponding catalytic activity will be lacking, so that the carbon material mixture cannot be fully reacted during the heating process, and finally the efficiency of the ultralight porous carbon material in absorbing radon in the air is greatly reduced.

[0076] (2) By comparing Comparative Example 2 with Examples 1-3 of the present invention, it can be seen that if the temperature of the muffle furnace calcination is greatly reduced to prepare the ultra-light porous carbon material, the carbon material mixture will not obtain sufficient heat within the specified reaction time, so that its reaction rate is slowed down and the reaction conversion rate is affected, which ultimately leads to a significant reduction in the absorption efficiency of the prepared ultra-light porous carbon material for radon.

[0077] (3) Compared with the above-mentioned Example 1, it can be seen that in Example 3, the pressure in the high-pressure reactor is reduced to prepare the ultra-light porous carbon material, which will lead to the lack of sufficient pressure in the carbon material mixture during the reaction process, resulting in the inability to smoothly generate pores inside the carbon material mixture, and thus the inability to construct a porous structure, making it difficult for the prepared ultra-light porous carbon material to absorb a large amount of radon.

[0078] (4) Comparative Example 4 does not add 13 The ultra-light porous carbon material prepared from straight-chain acetylene carbon using C as raw material lacks certain stability and adsorption performance. The porous structure generated is mostly a macroporous structure of 30nm to 200nm, and the corresponding specific surface area is significantly reduced, resulting in a significant reduction in the pollutant radon that can be absorbed.

[0079] In summary, the ultralight porous carbon material prepared by the present invention has certain stability and good adsorption capacity, can absorb free radon gas to protect human health, avoid causing diseases and heavy metal poisoning, and the ultralight porous carbon material itself is green and environmentally friendly, and no additional pollution will be generated during the overall absorption process.

[0080] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. An ultralight porous carbon material, characterized in that: The ultralight porous carbon material has a composite porous structure, including macropores with pore sizes of 30nm to 200nm, mesopores with pore sizes of 2nm to 30nm, and micropores with pore sizes of 1nm to 2nm. The specific surface area of ​​the ultralight porous carbon material is 2000m 2 / g~3000m 2 / g, relative density is 0.65~0.

90.

2. A method for preparing an ultralight porous carbon material according to claim 1, characterized in that: The method comprises the following steps: (1) mixing hydroxylated multi-walled carbon nanotubes with straight-chain acetylene carbon, adding an organic additive, heating in an oil bath and stirring to obtain a sol-like carbon material mixture; adding a modified molecular sieve to the sol-like carbon material mixture and calcining the mixture to obtain a calcined carbon material mixture; (2) mixing the calcined carbon material mixture with a metal salt solution and reacting the mixture in a high-pressure reactor to obtain a reacted carbon material mixture; (3) The carbon material mixture after the reaction is sequentially subjected to alkali washing, acid washing, water washing, impurity removal and drying to finally obtain an ultra-light porous carbon material.

3. The method for preparing an ultralight porous carbon material according to claim 2, characterized in that: The weight components of the hydroxylated multi-walled carbon nanotubes and the linear acetylene carbon in step (1) are 4-8 parts and 1-3 parts respectively; the carbon content of the hydroxylated multi-walled carbon nanotubes is 90%-95%; the carbon content of the linear acetylene carbon is 90%-95%; wherein the raw material of the hydroxylated multi-walled carbon nanotubes is 12 C; the raw material of the straight chain acetylene carbon is 13 C.

4. The method for preparing an ultralight porous carbon material according to claim 2, characterized in that: In step (1), the mass ratio of the organic auxiliary agent to the mixture is 10-15:50; the organic auxiliary agent is a mixed solution of epoxy organic amine and nitrilotriacetic acid, and the mass ratio of the epoxy organic amine to the nitrilotriacetic acid is 1:5-10.

5. The method for preparing an ultralight porous carbon material according to claim 2, characterized in that: In step (1), the mass ratio of the sol-like carbon material mixture to the modified molecular sieve is 9-10:0.5-0.8; the modified molecular sieve is HZSM-5 molecular sieve.

6. The method for preparing an ultralight porous carbon material according to claim 2, characterized in that: The calcination temperature in step (1) is 400° C. to 500° C., and the calcination time is 48 h to 96 h.

7. The method for preparing an ultralight porous carbon material according to claim 2, characterized in that: The reaction conditions in step (2) are as follows: the reaction pressure is 15 MPa to 25 MPa, the temperature is 150° C. to 200° C., and the reaction time is 24 h to 36 h.

8. The method for preparing an ultralight porous carbon material according to claim 2, characterized in that: The metal salt solution in step (2) is a calcium phytate solution; the mass ratio of the calcined carbon material mixture to the metal salt solution is (10-20):1; and the concentration of the metal salt is 0.01 mol / L-0.05 mol / L.

9. The method for preparing an ultralight porous carbon material according to claim 2, characterized in that: The alkaline solution used for the alkali washing is tetramethylammonium hydroxide solution; the mass ratio of the alkaline solution to the carbon material mixture after the reaction is (25-50):1; the acid solution used for the acid washing is dimethylbenzenesulfonic acid solution, and the mass ratio of the acid solution to the carbon material mixture after the alkali washing is (15-30):

1.

10. An application of an ultralight porous carbon material, characterized in that: The ultra-light porous carbon material described in claim 1 is used to absorb polluted gas radon.